2000
DOI: 10.1016/s1074-7613(00)00005-4
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ2 Is Essential in the Functions of B Cell and Several Fc Receptors

Abstract: Many receptors activate phospholipase Cgamma1 or -gamma2. To assess the role of PLCgamma2, we derived enzyme-deficient mice. The mice are viable but have decreased mature B cells, a block in pro-B cell differentiation, and B1 B cell deficiency. IgM receptor-induced Ca2+ flux and proliferation to B cell mitogens are absent. IgM, IgG2a, and IgG3 levels are reduced, and T cell-independent antibody production is absent. The similarity to Btk- or Blnk-deficient mice demonstrates that PLCgamma2 is downstream in Btk/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
426
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 440 publications
(463 citation statements)
references
References 52 publications
31
426
5
Order By: Relevance
“…We found that DC obtained from mice lacking PLCg2 [24] exhibited impaired capacity of antigen presentation and induction of T H 1 and T H 17 cells in response to b-glucan. Mechanistically, PLCg2-deficient DC failed to secrete cytokines, such as IL-12, IL-6 and IL-23, which are important for the generation of T H 1 and T H 17 cells.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…We found that DC obtained from mice lacking PLCg2 [24] exhibited impaired capacity of antigen presentation and induction of T H 1 and T H 17 cells in response to b-glucan. Mechanistically, PLCg2-deficient DC failed to secrete cytokines, such as IL-12, IL-6 and IL-23, which are important for the generation of T H 1 and T H 17 cells.…”
mentioning
confidence: 86%
“…PLCg2 À/À and BTK À/À -deficient mice have been previously described [24,43]. All animal studies were approved by the Washington University animal studies committee.…”
Section: Micementioning
confidence: 99%
“…However, PLCc2 contributes to the health and survival of both wild-type [2/20 PLCc2 -/-mice died within the 16-wk study period (Fig. 4A)] [17] and BLNK -/-mice via other undefined mechanisms.…”
Section: Differential Roles For Btk and Plcc2 In Pre-b Cell Tumor Supmentioning
confidence: 99%
“…A similar disease results from mutation of the human BLNK gene [9]. Mice lacking Btk [10][11][12], BLNK [13][14][15][16], or PLCc2 [17,18] have a milder phenotype with the predominant defect at the T2 to mature transition in the periphery. Btk -/-mice have a reduced frequency of Igk-expressing cells due to a role for Btk in Igk rearrangement in pre-B cells [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation